Assessing the relationships between information seeking, motives of using social media, and information sharing on haze and air pollution among IIUM students - Kasirye, Faiswal; Radwan, Hassan; Wok, Saodah; Saydul, Haque (Asian Scholar Network (002903215-H), 2020)
Haze and air pollution have become a major problem among the Association of Southeast Asian Nations (ASEAN) countries. Haze occurs almost every year, mainly due to activities done by farmers and factories within this region. Little research has been conducted to find out how this issue is addressed by institutions of higher learning such as the International Islamic University of Malaysia (IIUM), especially by linking information seeking and information sharing using social platforms. Therefore, this study was set out to examine the information seeking and information sharing on haze and air pollution among IIUM students. Specifically, this study aimed to determine the relationship between information seeking, information sharing, and the motives for using social media among IIUM students during the occurrence of haze and air pollution. The study utilized the agenda setting theory to explain the relationship between the variables. A total of 389 respondents participated in the study. Based on the quantitative research design and the survey method with questionnaire as a data collection tool, the study found that students normally look for information on haze and air pollution from the Internet. Findings also revealed the existence of a strong significant relationship between all the variables in the study. The results translate that the more the respondents desire to seek information on haze and air pollution, the more they will want to share it on social media platforms. Overall, the agenda setting theory is supported in this study.